How has the presence of an increasingly more global labor market softened the impact of the financial crisis 2008 for the U.K. economy?. (6th September 2019) - Floyd, David
Abstract: The changing labor market and a global labor force have helped keep costs down. This has helped reduce the impact of the recent financial crisis. Technological development has also contributed to this process. Policies have been adopted to open up global labor markets. Reforms have been made to make labor markets more flexible. This article considers the main factors that have motivated workers to go abroad. It also looks at the impact of a more diverse workforce on the economy since the financial crisis. The article draws on theories of mobility, employment, and global migration reports. Evidence would suggest that providing flexibility in the labor market is one of the keys to recovery from the financial crisis.